The analysis of carrier transport mechanism at the interface of BZOPET-GR Schottky contact - Jianhua Zhang; Yapeng Li; Jiqiang Jia; Zhaoyu Luo (Materials Research Express)
Through the hydrothermal technique, we successfully deposited boron (B)-doped zinc oxide nanorods (ZnO NRs) onto a polyethylene terephthalate (PET)/graphene (GR) flexible substrate, creating a B-ZnO/PET/GR Schottky contact. The ZnO NRs exhibited a well-defined hexagonal structure with a lattice constant size of approximately 0.502 nm, as evidenced by characterization results. X-ray Photoelectron Spectroscopy (XPS) analysis revealed a reduction in oxygen vacancies with increasing B ion doping. The current–voltage (I-V) characteristics of the Schottky contacts were systematically investigated over a temperature range of 160–300 K. As the temperature increased, the barrier height exhibited an upward trend, while the ideality factor decreased. This behavior was ascribed to barrier inhomogeneity at the Schottky contact interface. Employing a single Gauss distribution function for barrier height, we verified and elucidated this phenomenon, contributing to a comprehensive understanding of the observed temperature-dependent electrical properties.